Faktor-faktor yang Mempengaruhi Kunjungan Wisatawan ke Obyek Wisata Alaska Park Kota Banjarbaru - Azkia, Muhammad; Rahmini, Noor (PPJP ULM, 2024)
This research aims to determine the influence of distance factors, tourist expenditure and income on tourist visits to Alaska Park Tourism in Banjarbaru City. This research uses the accidental sampling method in sampling. Accidental sampling was carried out randomly from visitors to Alaska Park. Data was processed using Multiple Linear Regression analysis. The data source, namely primary data, comes from direct interviews with Alaska Park visitors using a questionnaire that meets the criteria. The research results explain that the variables of distance, tourist expenditure and overall income have a significant effect on tourist visits to rides at Alaska Park Tourism. The magnitude of the effect was 71.3%, and the remaining 29.7% was explained by other factors not included in the study. The factor that has the most dominant influence on tourist visits to rides at Alaska Park Tourism in Banjarbaru City is tourist expenditure.